Respuesta :

9514 1404 393

Answer:

  x

Step-by-step explanation:

There is already an expression given for x, so that is the easiest variable to substitute for.

Substituting for x using the second equation, you have ...

  -3(-2y+14) +y = -14

  6y -42 +y = -14

  7y = 28

  y = 4

  x = -2(4) +14 = 6

The solution is (x, y) = (6, 4).

_____

Substitution for x is the easiest.

__

The first equation could be rearranged to give an expression for y:

  y = 3x -14

Then that can be used to substitute for y in the second equation. My lazy brain judges that to be more work.